2012
DOI: 10.5001/omj.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus: Maternal and Perinatal Outcomes in 220 Saudi Women

Abstract: GDM is recognized to be associated with increased rates of adverse maternal and neonatal outcomes, which are supported by the findings of this study. Even the mild form of GDM seems to have significant consequences for women and their offspring and is recommended to be aggressively treated. Evidence suggests that early diagnosis and strict control of blood sugar levels throughout the pregnancy can significantly reduce maternal and fetal complications. A multicenter, randomized controlled trial, based on univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
77
6
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 22 publications
16
77
6
6
Order By: Relevance
“…6 Similar results were reported in the French study by Billionet et al and they commented that GDM women on insulin are at a higher risk for hypertensive disorders in pregnancy than those on diet mono therapy alone. 7 However, in their study conducted in Netherlands, Koning et al did not find any significant difference in the two groups regarding occurrence of gestational hypertension which was supported by our present study.…”
Section: Discussionsupporting
confidence: 78%
“…6 Similar results were reported in the French study by Billionet et al and they commented that GDM women on insulin are at a higher risk for hypertensive disorders in pregnancy than those on diet mono therapy alone. 7 However, in their study conducted in Netherlands, Koning et al did not find any significant difference in the two groups regarding occurrence of gestational hypertension which was supported by our present study.…”
Section: Discussionsupporting
confidence: 78%
“…There is an incidence of 16.6% hyperbilirubinaemia which is comparable to the Polish study 9 though much higher than 8% reported from studies in India 10 and Saudi 6 and lower than 23 and 29.3% in studies from Saudi 9 and Kolkata 7 respectively. The incidence of hypoglycaemia in our study falls within the range reported in various studies of 2.7% to 16% 6,7,9,11 . Though the study 3 on impact of glycaemic control on neonatal outcome shows that macrosomia and still birth have declined with good glycaemic control, study on early onset gestational diabetes continue to show incidence of macrosomia 1 as we have reported.…”
Section: Discussionsupporting
confidence: 72%
“…The association of pregnancy induced hypertension in gestational diabetes and increased incidence of caesarean section that we see in our study has been documented 6,7,8 . Multiple studies 6,7,9,10 have reported increased premature onset of labour/preterm deliveries which can explains the high incidence of preterm and low birth weight babies. As a result, our mean birth weight of new-borns remained within normal range as seen in the Polish study though other studies have reported large babies 2,8,11 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Many studies showed that screening, detection, and treating GDM can greatly reduce maternal, fetal, and neonatal morbidities [12].…”
Section: Introductionmentioning
confidence: 99%